Contributions of Liquid-Based (Papanicolaou) Cytology and Human Papillomavirus Testing in Cotesting for Detection of Cervical Cancer and Precancer in the United States - Kaufman, Harvey W (Am J Clin Pathol, 2020)
OBJECTIVES: Given the recent debate challenging the contribution of cytology in cervical screening, we evaluated results of liquid-based cytology (LBC) and human papillomavirus (HPV) testing in cotesting preceding cervical cancer (CxCa) and precancer diagnoses in a national, heterogeneous population. METHODS: We assessed the results of cotesting, performed by Quest Diagnostics, in 13,633,071 women 30 years and older, tested 2010 to 2018. Cotest results preceding CxCa or precancer diagnoses were analyzed and stratified by histopathology. RESULTS: Among all screening results, 1,615 cotests preceded 1,259 CxCa diagnoses, and 11,164 cotests preceded 8,048 cervical precancer diagnoses. More women who were subsequently diagnosed with CxCa within 1 year were identified by the LBC result than by the HPV result (85.1%, 1,015/1,193 vs 77.5%, 925/1,193). Among all women with CxCa, the overall rate of nondetection was 13.1% (212/1,615) for cotesting results (LBC negative/HPV negative) and this rate increased substantially when testing exceeded 12 months compared to within 1 year prediagnosis of either CxCa or precancer. CONCLUSIONS: Analysis of 9-year cotest results from a national reference laboratory confirms the value of LBC element in cotesting. This supports that LBC/HPV cotesting enhances screening for the identification of CxCa in women 30 years and older, more so than LBC or HPV alone within cotesting.